Dog training - Zeigenfuse, Mary Ann Rombold; Volhard, Wendy (--For dummies., 2026)
"An easy, hands-on guide to training your dog. Interested in learning about the best, most effective training methods for dogs of all ages, personalities, and breeds? In Dog Training for Dummies, a team of veteran dog trainers and dog training educators walks you through a comprehensive collection of commands, techniques, and breed-specific strategies for modifying and managing your dog's behaviors. You'll learn how to housetrain your dog, create a happy home and environment for your pet, and solve the most common dog behavior problems"--